The Effect of Heat Input on Welding Combination of GTAW and SMAW SA537 Material on Mechanical Properties and Microstructure - Tarmizi Tarmizi; Nabil Aga Hananda; Irfan Irfan (Department of Naval Architecture - Diponegoro University, 2022)
The combination of GTAW (Gas Tungsten Arc Welding) and SMAW (Shield Metal Arc Welding)processes on SA537 Class 2 carbon steel using variations of heat input is the main choice to get thebest quality welded joints. This research aims to joint SA537 Class 2 material using the GTAW andSMAW process with heat input variations to get the best joint and determine the joint resultsmechanical properties and microstructure analysis. The experimental method uses a combination ofGTAW and SMAW processes with a single V butt joint design, groove angle of 60o, root face 2 mm androot gap of 4 mm as many as 7 passes, and variations in heat input of 2.5 kJ/mm, 2.8 kJ/mm and 3.2kJ/mm. According to ASME section IX, the mechanical testing results showed that the specimen witha heat input of 2.8 kJ/mm gave optimum results with the highest tensile strength of 480 MPacompared to the other two specimens, and there were no cracks when tested for bending The higherthe heat input, the greater the decrease in the percentage of ferrite. Using a heat input of 2.8 kJ/mm inthis study provides a weld result with better mechanical properties and microstructure than the useof heat input of 2.5 kJ/mm and 3.2 kJ/mm.